2001
DOI: 10.1002/jnr.1039
|View full text |Cite
|
Sign up to set email alerts
|

Glial transporters for glutamate, glycine and GABA I. Glutamate transporters

Abstract: The termination of chemical neurotransmission in the CNS involves the rapid removal of neurotransmitter from synapses by specific transport systems. Such mechanism operates for the three major amino acid neurotransmitters glutamate, γ‐aminobutyric acid (GABA) and glycine. To date, five different high‐affinity Na+‐dependent glutamate (Glu) transporters have been cloned: GLT1, GLAST, EAAC1, EAAT4 and EAAT5. The first two are expressed mainly by glial cells, and seem to be the predominant Glu transporters in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(34 citation statements)
references
References 117 publications
0
34
0
Order By: Relevance
“…EAAT3 (called EAAC1 in the rodent) is predominantly expressed in the cerebral cortex, basal ganglia and hippocampus. 257 Post-mortem studies in schizophrenic patients revealed alterations in gene expression of glutamate transporters. 258,259 In addition, preclinical studies demonstrated that chronic treatment with clozapine or haloperidol can downregulate EAAT3 in the infralimbic cortex and hippocampal CA2.…”
Section: Dopaminergic Agentsmentioning
confidence: 99%
“…EAAT3 (called EAAC1 in the rodent) is predominantly expressed in the cerebral cortex, basal ganglia and hippocampus. 257 Post-mortem studies in schizophrenic patients revealed alterations in gene expression of glutamate transporters. 258,259 In addition, preclinical studies demonstrated that chronic treatment with clozapine or haloperidol can downregulate EAAT3 in the infralimbic cortex and hippocampal CA2.…”
Section: Dopaminergic Agentsmentioning
confidence: 99%
“…Astrocytes predominantly express two transporters that are used in this process: the Lglutamate/L-aspartate transporter (GLAST-1) and the glial L-glutamate transporter (GLT-1), also called excitatory amino acid transporters (EAAT1 and EAAT2, respectively) (Gadea and Lopez-Colome, 2001). Normally, concentration gradients favor the transport of glutamate into astrocytes.…”
Section: Reverse Operation Of Glutamate Transportersmentioning
confidence: 99%
“…Two of these, GLAST and GLT1, dominate glutamate transport in the CNS (Gadea and Lopez-Colome 2001). Drugs are available with specificities that can distinguish GLT1 from GLAST and EAAC1 (Namura et al 2002;Wang et al 1998).…”
Section: Pharmacologymentioning
confidence: 99%